Hubungan Pengetahuan Tentang Kanker Payudara Dengan Perilaku Sadari (Periksa Payudara Sendiri) - Rini Deska; Dewi Ayu Ningsih; Lisa Luviana (LPPM Sikes Panca Bhakti Bandar Lampung, 2019)
Cancer incidence in Indonesia (136.2 / 100,000) ranks 8th in Southeast Asia and 23rd in Asia. In Indonesia, the incidence of cancer is more dominated by breast cancer, which is 42.1 per 100,000 population. Breast cancer that is found at an early stage is likely to heal approaching 95%, so that early detection tests are needed. One of the early breast cancer detection programs is Self Breast Examination (BSE) (P2PTM Ministry of Health, Republic of Indonesia, 2017). In 2016, as many as 53.7% of the population did not do BSE. This study aims to determine the relationship of knowledge about breast cancer with BSE behavior (Check Breast Self) in AKBID Panca Bhakti Bandar Lampung students in 2019. This study uses an observational analytic design through a cross-sectional approach to 133 midwifery students. The statistical analysis used was the chi-square test. The results showed that most midwifery students' knowledge was in the good category (43.8%). BSE behavior of midwifery students was mostly in the less category (73.7%). Statistically, there is no proven relationship between knowledge about breast cancer and BSE behavior (ρ = 0.420). Further research needs to be done with experimental methods in the form of pre-test and post-test about the effectiveness of video with BSE behavior.